Pimarane, abietane, and labdane diterpenoids from Euphorbia pekinensis Rupr. and their anti-tumor activities. (May 2022) - Chen, Yan-Yan; Zeng, Xiao-Tao; Xu, Ding-Qiao; Yue, Shi-Jun; Fu, Rui-Jia; Yang, Xue; Liu, Zhao-Xi; Tang, Yu-Ping
Abstract: Chemical investigation of the roots of Euphorbia pekinensis Rupr. led to the isolation of five undescribed labdane diterpenoids "(4 S, 5 S, 9 R, 10 S, 13 R )-18- O -galloyl-labda-8(17), 14(15)-dien-13-ol; (4 S, 5 S, 9 R, 10 S, 13 R )-13-hydroxy-labda-8(17), 14(15)-dien-18-one; (4 S, 5 S, 9 R, 10 S, 13 R )-18- O -acetyl-labda-8(17), 14(15)-dien-13-ol; (4 S, 5 S, 9 R, 10 S )-labda-8(17), 13(16), 14(15)-trien-18-ol; (5 R, 6R, 9 R, 10 S, 13 R )-labda-8(17), 14(15)-dien-6, 13-diol", two undescribed pimarane diterpenoids "(2 R, 5 S, 9 R, 10 S, 12 R, 13 R )-2, 12-dihydroxy-isopimara-7, 15-dien-3-one; (5 S, 9 R, 10 S, 12 R, 13 R )-2, 12-dihydroxy-isopimara-1, 7, 15-trien-3-one)", together with nine known diterpenoids, including three pimarane-type "(3β, 11α, 13α)-3, 11-dihydroxypimara-7, 15-diene-2, 12-dione; (11R, 12S)-2, 11, 12-trihydroxy-ent-isopimara-1, 7, 15-trien-3-one; isopimara-7, 15-dien-3β-ol)", five abietane-type "helioscopinolide A-C; helioscopinolide E; helioscopinolide I″, and one lathyrane-type "jolkinol B". The structures of these compounds were elucidated by analysis of HRESIMS, 1D NMR, 2D NMR, and X-ray diffraction. These sixteen compounds were evaluated for cytotoxic activity in vitro against three human cancer cell lines, U-937, LOVO, and K-562. Jolkinol B exhibited IC50 of 3.60 μM and 8.44 μM against U-937 and LOVO cell lines, (4 S, 5 S, 9 R, 10 S, 13 R )-18-O-galloyl-labda-8(17), 14(15)-dien-13-ol displayed IC50 of 5.92 μM against U-937 cell lines, isopimara-7, 15-dien-3β-ol showed IC50 of 0.87 μM against K-562 cell lines. Graphical abstract: Image 1 Highlights: Sixteen diterpenoids were isolated from Euphorbia pekinensis Rupr. Undescribed two pimarane diterpenoids and five labdane diterpenoids were isolated. All the isolated compounds were evaluated for their cytotoxicity.